Analysis of Factors Influencing Youth Participation in Agricultural Production Case Study of Manyatta Sub County, Embu County - Mwao, Karungwa Emmanuel (University of Embu, 2020)
This study sort to analyze the factors that influence the youth participation in agriculture production in Manvatta sub county Embu County, Kenya. This research was necessitated by the fact that, despite the awareness by the Kenyan government and her development partners, that the reliance on agriculture for food production and food security at domestic, regional and global level depends on youth creativity and productive force and that, youth participation in agriculture is an important source of employment to the youth. Agriculture remains the backbone of Kenyan economy. In Manyatta Sub County, the rate of unemployment is high and many youths are migrating to towns in search for jobs with little or no success. This is attributed by the fact that farming to youth is expensive and meant for the older generation. Studies shows that countries that depend heavily on agriculture are unable to create enough job opportunity in the non-agricultural sectors hence unemployment is high in the third world countries Kenya included. The study was based on the following objectives; to determine the influence of access to land on youth participation on agricultural production; to determine influence of access to credit on youth participation on agriculture. The research design employed was cross sectional since data was taken once from the samples in a three span of time. The targeted population for the study was 117 registered farmers in Manyatta Sub County. Primary data was collected through administering semi structured questionnaires. Descriptive and inferential statistics was used to analyze the quantitative data. Descriptive statistics was used to summarize the data. Inferential statistics (Pearson's correlation analysis) was used to explore the relationship between dependent and independent variables.